Transitioning diets: a mixed methods study on factors affecting inclusion of millets in the urban population - Suruchi Singh; Vidya Vemireddy (BMC, 2023)
Abstract Background The increasing health challenge in urban India has led to consumers to change their diet preferences by shifting away from staple cereals and making way for healthier foods such as nutri-cereals like millets and other diverse food groups. Taking the case of millets, this study seeks to uncover the exact drivers for this shift of consumers away from a traditional cereal dense diet to a nutritionally more diverse diet that includes nutri-cereal. We also look at deterrents that dissuade consumers from shifting to millets. Method We use primary data by surveying respondents through interviews and focused group discussions and online questionnaires. A total of 20 personal consumer interviews and 4 focus group discussions having 8-12 members each were conducted to arrive at the measures for the study. We use logistic regression and Structural Equation Modeling for data analysis. Responses were obtained across major metropolitan cities and tier 2 cities of India thus ensuring representation of geographical, cultural and diet diversity. 875 participants' responses were analysed for results. Results Health reasons and social networks are the major drivers for shift to millets while lack of awareness, lack of easy availability, high prices, lack of branded products, family being averse to switching to millets and lack of attractive promotional cashbacks and discounts are major deterrents to trying out millets. Conclusions Diet focussed interventions are urgently needed to curb rising diet related non communicable diseases. Government policies aimed at greater production of millets, running awareness campaigns on mass media and private sector initiatives aimed at generating better value added market offerings could lead the way.